The impact of student computer competency on e-learning outcomes: A path analysis model of virtual learning infrastructure, collaboration, and access to electronic facilities - Sharif-Nia, Hamid (Wiley, 2024)
Aim This study explored the influence of student computer competency on e-learning outcomes among Iranian nursing students and examined its mediating role in the relationship between virtual learning infrastructure, student collaboration, access to electronic facilities, and e-learning outcomes.